A Low Cost and High Reliability Permanent Magnet Synchronous Motor Control Platform: Design of Speed Sensorless Servo Controller Based on MRAS - Tao Huang, Xiaoteng Tang, Xinliang Wu (Forest Chemicals Review, 1970)
It’s necessary for engineers and designers to get a low-cost and reliable permanent magnet synchronous motor control platform, so a permanent magnet synchronous motor sensorless servo control platform based on TI's low-cost DSP chip TMS320F2812 is designed in this paper. In the aspect of hardware, the design of various signal acquisition circuits and motor drive circuits are introduced in detail. At the same time, special attention is paid to the isolation of strong and weak current and the protection measures of intelligent power module. In the aspect of software, taking Model Reference Adaptive System approach as the core, the relationships and implementation methods of AD adoption, stator volotage calculation, CLARK Transform, estimation of flux linkage and torque, speed estimation are introduced. At the end of the paper, three experiments are carried out: PWM wave generation, position and speed estimation signal verification and system closed-loop. The experimental results verify that the designed control platform has strong control function, stable working performance, low cost because of abandoning speed/position sensor such as encoder. A wide application prospect can be expected.